Unconventional teaching resources and their role in the organization of geography teaching at schools (Geosaberes, 2018)
The teaching of geography taught at schools over the times with the use of encyclopedism, has had a change of re-signification of contents and themes, daily approached. This re-signification involves the development of different types of contents (conceptual, procedural and attitudinal), as well as the use of didactic resources. This article presents results of a bibliographical survey about the theme: "Didactic Resources and Teaching of School Geography" and it aims to broaden the knowledge of teachers about the potential of non - conventional didactic resources which make Geography leaning more meaningful for students of basic education.